Ascorbic acid contents in selected vegetables in relation to variety, growing site, year and storage - Jana Matějková; Kristína Petříková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2010)
This work give results from analyses of variety, growing site, year and storage influence on the ascorbic acid content by selected vegetables: carrot (Daucus carota L.), parsley (Petroselinum crispum Nyman ex A. W. Hill), onion (Allium cepa L.), garlic (Allium sativum L.) and leek (Allium porrum L.). The evaluation carried on during the years 2004 to 2006.The variety influence on ascorbic acid was statistically significant by carrot, parsley root and also parsley leaves and by garlic. In carrots had late varieties Olympia and Tinga significant higher vitamin C content (more than over 60 %) compared to early to half-late varieties Delicia, Kráska, Stupická and Nerac F1. The growing site influence was significant only by parsley leaves and onion. The influence of the growing year was one of the most important factors, which influenced vitamin C contents in selected vegetables – except of carrot was this factor statistically significant by all sorts. Changes in vitamin C content in growing years were induced above all by different climatic conditions (temperatures and rainfall courses). Higher ascorbic acid content was by garlic in the year 2005, when lower temperatures during July were noted compared to year 2004. In parsley root and leaves, onion and leek was noted higher ascorbic acid content in year 2005, when average temperatures in August were as far as 2°C lower than in year 2004. In the case of leek could the increase of ascorbic acid in year 2005 result also from minimal rainfall during October in comparison with October 2004. By all storaged vegetables was noted statistically significant decrease of vitamin C after 30-days storage. The losses of vitamin C were highest in carrot (45 %), followed by parsley (25 %), garlic (24 %) and onion (22 %).Vitamin C content was the highest by parsley leaves (1692 mg . kg−1), parsley contained high vitamin C amounts also in root (515 mg . kg−1). Leek varieties contained 281 to 297 mg . kg−1 of vitamin C, garlic varieties 105 to 132 mg . kg−1, onion varieties 94 to 104 mg . kg−1 and carrot varieties 58 to 117 mg . kg−1 vitamin C.